EDUCATIONAL ACHIEVEMENTS IN STUDENTS 'SELF-ASSESSMENT ECONOMIC SPECIALTIES OF HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2008)
In article the self-estimation of educational achievements of students of economical specialties and factors which influence positive dynamics of the students' educational achievements are considered.